Bentuk Deiksis Tempat dalam Penerjemahan Deiksis dari Bahasa Indonesia ke Bahasa Inggris (Studi Semantik-Pragmatik pada Novel Negeri 5 Menara Karya Ahmad Fuadi) - Hasanah, Luluk Ulfa (Jurnal Penerjemahan, 2018)
The research aims to obtain a shape description of the place deixis in the deixis translation from Bahasa Indonesia into English. The place deixis at the Novel Negeri 5 Menara is a focus of this research. A content analysis method with qualitative approach is used as a method on this research. There are 49 data that relating to the translation of place deixis. The results of this were found as follows. The form of translation of place deiksis can be divided into 5 types, namely the place deixis in the room, the place in outside of the room, the place that is near the speaker, the place that is far from the speaker, and the place with the name. From the five types of place deixis is translated from words to words, words to phrases, phrases to words, and phrases to phrases. Keywords : Translation, The Deixis Translation, The Place Deixis